2014
DOI: 10.1111/tmi.12340
|View full text |Cite
|
Sign up to set email alerts
|

Duration of residence and disease occurrence among refugees and family reunited immigrants: test of the ‘healthy migrant effect’ hypothesis

Abstract: Abstractobjectives The 'healthy migrant effect' (HME) hypothesis postulates that health selection has a positive effect on migrants' health outcomes, especially in the first years after migration. We examined the potential role of the HME by assessing the association between residence duration and disease occurrence.methods We performed a historical prospective cohort study. We included migrants who obtained residence permits in Denmark between 1 January 1993 and 31 December 2010 (n = 114 331). Occurrence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 25 publications
9
101
1
Order By: Relevance
“…Immigrant cohorts with a longer duration of residence in their new country were at an increased risk of IHD and stroke in most studies. 27,30,33 However, in intergenerational studies, risk levels appeared to converge to that of the host population, as has been shown in previous studies. 48 This observation might be explained by immigrants' adoption of the lifestyles of their host country increasing with greater duration of residence regardless of their risk at the time of arrival.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Immigrant cohorts with a longer duration of residence in their new country were at an increased risk of IHD and stroke in most studies. 27,30,33 However, in intergenerational studies, risk levels appeared to converge to that of the host population, as has been shown in previous studies. 48 This observation might be explained by immigrants' adoption of the lifestyles of their host country increasing with greater duration of residence regardless of their risk at the time of arrival.…”
Section: Discussionsupporting
confidence: 55%
“…27,30,32,33 In England and Wales, duration of residence was associated with an increased risk of stroke mortality among Caribbean immigrants (hazard ratio, 1.38 per year of residence; 95% CI, 1.10-1.74), 32,33 and in South Asian immigrants, stratified according to age, a trend toward increased IHD mortality risk with each year of residence was observed in all age groups; however, this was not statistically significant. 32 In Denmark, IHD risk among family members reunited with other immigrants appeared to increase with duration of residence; however, the risk of stroke appeared unchanged.…”
Section: Risk With Duration Of Residencementioning
confidence: 53%
See 2 more Smart Citations
“…6, 17, 18 Moreover, incidence may be higher among refugees than among immigrants more generally. 19 In recent years, the European Union has experienced the largest inflow of immigrants and refugees since the end of the Second World War. The current wave of immigration includes a majority of individuals from the Middle East and North Africa, where T2D prevalence is the highest of any region worldwide: 11% among adults aged 20–79 in 2013.…”
Section: Introductionmentioning
confidence: 99%